Spanish Theme Parks: The Continuity Paradox After a Decade of Operations - Bernabe Escobar Perez; Silvia Fresneda Fuentes; Antonio Lobo Gallardo (Journal of Accounting, Business and Management (JABM), 2009)
Theme Parks are getting more relevant within the tourism industry. They generate opposed positions in specialized studies. On the one hand, there are those who defend (Economics Research Associates, 2003) them by affirming that they are one of the most promising tourism segments. On the other hand, there are others who argue that they are not so profitable businesses. This paper analyzes the historical evolution and the current situation of the Spanish Theme Parks through their financial information. The goal is to determine, from a technical point of view, some of the causes behind their existence and paradoxical continuity. In order to reach our objectives, we have studied the evolution of the main financial ratios of the sector, according to the information contained in their Balance Sheet, Profit and Loss Account. The main conclusion, then, reveals that their financial current situation and the foreseeable evolution are negative and their continuity seems to be based on political reasons more than purely economic and financial ones.